Proposed a WebRTC Data Communication Using Effective Signalling Protocol - Mahmood, Sanabil A. (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Web Real-Time Communication (WebRTC) is designed to permit the co-occurrence of audio, video, and data communications. However, an effective signalling mechanism that setup, establish and end communication between peers has not been specified in WebRTC. This paper designs and implements an effective WebRTC signalling mechanism for data communication compared with the common existing applications and current reviews. Moreover, it focuses on the limitations of multi-browsers communication and data. As long as no elaboration specifies how the signalling mechanism can be used in WebRTC because it does not understand the concept of sessions but rather that of streams, which create and consumes media flows. In addition, this research will elaborate on the related work and analyse the communication quality of data communications, such as data, audio, and video. Keywords: Web Real-time Communication (WebRTC); Signalling Protocols.